A comparative analysis of the effect of individualistic, unique hard- and soft-tissue parameters of the face on buccal corridors in adolescents and adults with Angle's Class I and Angle's Class II Division 1 malocclusion - Maitreye Priyadarshini; Purva Joneja; Oshin Pawar; Shivani Bhuyan; Shama Samreen; Shwetneel Singh (Wolters Kluwer Medknow Publications, 2024)
Background and Objectives: This study was designed to determine the relationship between the parameters: buccal corridor, buccal corridor linear ratio (BCLR), upper intercanine width, intermolar width, and premolar basal arch width on a posed smile in adolescents and adults. The buccal corridor affects smile esthetics; hence, it is important to see its correlation with intercanine width. In addition, the study aimed to determine if the buccal corridor changes adversely in Class I and Class II Division 1 malocclusion patients and during growth. Materials and Methods: Posed smile and standard full-front face photographs of 150 patients were taken. Group A consisted of 50 adolescent patients between the ages of 11 and 14 years, divided equally based on malocclusion type. Group B consisted of 100 young adults between the ages of 18 and 25 years, divided equally into Class I and Class II Division 1 malocclusion. The parameters calibrated in the photographs were: upper intercanine distance, intercanthal distance, intercommisure width, difference between intercanthal and intercommisure width, distance between the last visible teeth in the maxilla, and BCLR. Results: The results of this study were analyzed using one-way ANOVA and Chi-square tests. The analysis showed a significant correlation between BCLR, intercanine width, distance from the last visible teeth, intercanthal distance, and intercommisure width, and their difference varied significantly among males and females, with P < 0.05. Conclusion: This study concluded that the buccal corridor and intercanine width vary with age and gender. The buccal corridor is usually wider in young adults than in adolescent children.